2013
DOI: 10.1111/eip.12082
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapeutic interventions in individuals at risk of developing bipolar disorder: a systematic review

Abstract: Psychotherapeutic treatments are a reasonable starting point for At-Risk-BD subjects when symptom severity, distress and impairment are sufficiently significant to initiate treatment. Ongoing studies will further clarify the effectiveness and timing of psychotherapeutic interventions for At-Risk-BD individuals and whether or not they should be given alone or in conjunction with other treatments. Large multi-site studies with standardized procedures/manuals are needed to advance the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 59 publications
0
21
0
2
Order By: Relevance
“…31 Our map identified more than four times as many studies of the early stages of bipolar disorder as the previous systematic reviews in the specialty (29 studies as compared with zero to seven studies identified in the systematic reviews) 27–30 . However, comparison with existing evidence maps of psychosis and depression indicates that work in bipolar disorder is lagging behind these areas of investigation.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…31 Our map identified more than four times as many studies of the early stages of bipolar disorder as the previous systematic reviews in the specialty (29 studies as compared with zero to seven studies identified in the systematic reviews) 27–30 . However, comparison with existing evidence maps of psychosis and depression indicates that work in bipolar disorder is lagging behind these areas of investigation.…”
Section: Discussionmentioning
confidence: 78%
“…However, these studies do not address the potential benefits of therapy to high-risk or subsyndromal cases of bipolar disorder (stages 0–1), or to first-episode cases in young people (stage 2). Four systematic reviews 27–30 of psychological interventions for mixed populations of children, adolescents, young adults, and those people at high risk or having already had a first episode of bipolar disorder, have identified 0–5 completed and two ongoing studies at the time of writing. These findings might suggest that only few investigations are undertaken in this area.…”
Section: Bipolar Disorder: Clinical Staging and Psychological Therapiesmentioning
confidence: 99%
“…When considering the possibility of emergent BD in an adolescent, it is not sufficient to screen for symptoms of BD, given the limitations of the DSM (Kowatch et al, 2004) and non-specificity of common symptoms such as irritability and impulsivity (Pfennig et al, 2014). Furthermore, various factors can trigger mania without a diagnosis of BD being appropriate, such as substance use, sleep deprivation and thyroid conditions (Kowatch et al, 2004).…”
Section: Signs Of Future Bd In Adolescentsmentioning
confidence: 99%
“…The prevalence is as low as 1.8% (Van Meter et al 2011) in the pediatric population; however, when broader diagnostic criteria are used, the rates rise up to 6.7% in the United States (Van Meter et al 2011). BD is associated with significant morbidity and oftentimes the pharmacotherapy may be inadequate in resolving symptoms (Deckersbach et al 2014;Pfennig et al 2014). More than 50% of patients diagnosed with BD have onset of their illness prior to 20 years of age (Lish et al 1994;Morselli et al 2003;Kessler et al 2005a;Blumberg 2008), and subsyndromal symptoms may be experienced years earlier (Chang 2007).…”
Section: Introductionmentioning
confidence: 99%